2022
DOI: 10.1007/s40615-022-01272-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Race/Ethnicity and Social Vulnerability on COVID-19 Positivity, Hospitalization, and Death in the San Francisco Bay Area

Abstract: Background Higher COVID-19 incidence and morbidity have been documented for US Black and Hispanic populations but not as clearly for other racial and ethnic groups. Efforts to elucidate the mechanisms underlying racial health disparities can be confounded by the relationship between race/ethnicity and socioeconomic status. Objective Examine race/ethnicity and social vulnerability effects on COVID-19 outcomes in the San Francisco Bay Area, an ethnically and socioeconomically diverse region, using geocoded patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Of the 7,280 individuals testing positive for COVID-19, 696 (6.5%) were hospitalized at UCSF Health. As noted previously [9], although Asian patients had the second-lowest rates of testing positive for COVID-19 amongst the four racial/ethnic groups, Asian patients demonstrated the highest rate of hospitalization. To investigate this observation further, a logistic regression was performed that included race/ethnicity, sociodemographic factors, and biomedical risk factors as independent variables, and COVID-19 hospitalization as the dependent variable.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Of the 7,280 individuals testing positive for COVID-19, 696 (6.5%) were hospitalized at UCSF Health. As noted previously [9], although Asian patients had the second-lowest rates of testing positive for COVID-19 amongst the four racial/ethnic groups, Asian patients demonstrated the highest rate of hospitalization. To investigate this observation further, a logistic regression was performed that included race/ethnicity, sociodemographic factors, and biomedical risk factors as independent variables, and COVID-19 hospitalization as the dependent variable.…”
Section: Resultssupporting
confidence: 74%
“…In the intervening century since the 1918 influenza pandemic, despite an overall demographic shift toward a more pluralistic and multi-racial society in many regions of the United States, racial and ethnic disparities continue to persist in various domains, including in health, and are evident not just for Black Americans but for Americans belonging to a range of racial and ethnic minorities. During the current coronavirus pandemic, Black and Hispanic individuals have tested positive for COVID-19 at higher rates than White individuals [5, 6, 7, 8], and COVID-19-related hospitalizations and deaths have disproportionately affected American Indian, Asian, Black, and Hispanic persons [9, 10, 11, 12]. Despite widespread recognition of racial health disparities dating back more than a century, considerable disagreement and uncertainty remain as to whether the principal cause of health inequities is more firmly rooted in race or in racism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in several geographic areas of the United States, a strong association between living in a disadvantaged area and the risk of getting SARS-CoV-2 infection and of being hospitalized for SARS-CoV-2 infection has been reported [30]. On the other hand, a study in San Francisco reported a relationship between social vulnerability and COVID-19 hospitalization rates, although this study noted that COVID-19 outcomes were not systematically explained by increased social vulnerability, as this relationship occurred only in white people but not in those of other ethnic groups [31]. Our data do not support that living in an area of higher social deprivation increases the likelihood of being hospitalized for COVID-19.…”
Section: Discussionmentioning
confidence: 61%